Evaluasi Sinergitas Program CSR Bank BCA Ponorogo dalam Mendukung Kebijakan Pemerintah Daerah untuk Percepatan Penurunan Angka Stunting - Erysa Nimastuti; Sri Roekminiati; Ika Devy Pramudiana; Sapto Pramono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The acceleration of stunting reduction in Ponorogo Regency faces challenges regarding the complexity of the issue and regional fiscal constraints, necessitating strategic cross-sectoral collaboration. This study aims to evaluate the synergy of Bank BCA's Corporate Social Responsibility (CSR) program through the